2010
DOI: 10.1007/s00259-010-1517-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and dosimetry of 18F-EF5 in cancer patients with preliminary comparison of 18F-EF5 uptake versus EF5 binding in human glioblastoma

Abstract: Purpose The primary purpose of this study was to assess the biodistribution and radiation dose resulting from administration of 18F-EF5, a lipophilic 2-nitroimidazole hypoxia marker in ten cancer patients. For three of these patients (with glioblastoma) unlabeled EF5 was additionally administered to allow the comparative assessment of 18F-EF5 tumor uptake with EF5 binding, the latter measured in tumor biopsies by fluorescent anti-EF5 monoclonal antibodies. Methods 18F-EF5 was synthesized by electrophilic add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…We found that the EDE value for 18 F-FAZA (0.015 mSv/MBq) was between the values for 18 F-FETNIM (0.017 mSv/ MBq) and 18 F-FMISO (0.013 mSv/MBq), whereas 18 F-EF5 had an EDE of 0.029 mSv/MBq. The higher doses for 18 F-EF5, both for urinary bladder and EDE, are probably due to the authors' assumption-in the evaluation of doses-that no activity was excreted (25). 18 F-FAZA PET/CT has also been found to be valuable as a prognostic biomarker in oncologic patients (27) and as a guide to tailoring treatment approaches such as hypoxia-directed intensitymodulated radiotherapy (14,28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the EDE value for 18 F-FAZA (0.015 mSv/MBq) was between the values for 18 F-FETNIM (0.017 mSv/ MBq) and 18 F-FMISO (0.013 mSv/MBq), whereas 18 F-EF5 had an EDE of 0.029 mSv/MBq. The higher doses for 18 F-EF5, both for urinary bladder and EDE, are probably due to the authors' assumption-in the evaluation of doses-that no activity was excreted (25). 18 F-FAZA PET/CT has also been found to be valuable as a prognostic biomarker in oncologic patients (27) and as a guide to tailoring treatment approaches such as hypoxia-directed intensitymodulated radiotherapy (14,28).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these disadvantages, other nitroimidazole PET tracers with high avidity for hypoxic tissue have been investigated and developed, including 18 F-FETNIM (23), which is more hydrophilic than 18 F-FMISO and washes out more rapidly from normal oxygenated tissues, theoretically allowing a higher tumor-to-background ratio (8). In addition, another hypoxia tracer, with a more stable but also more complex labeling chemistry, is represented by 18 F-EF5 (8,24,25). This tracer is slightly more lipophilic than the formerly described compounds and has been investigated in various tumors in animal and clinical studies (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 F]EF-5 contains five fluorine atoms and is a very lipophilic molecule in comparison with other nitroimidazole derivatives (Koch et al, 2010;Lin et al, 2012). In a research reported by Koch et al (2010), three patients with gliobastoma were assessed by [ 18 F]EF-5 PET. Binding was also measured ex vivo on tumor biopsies by immunohistochemistry using fluorescent anti-EF-5 monoclonal antibody (Koch et al, 2010).…”
Section: F Tumor Microenvironment Imagingmentioning
confidence: 99%
“…However, other markers of hypoxia have been developed that could have broader applicability in NSCLC. The 2-nitroimidazole 18 F-EF5 has also been used to image glioblastomas, but its use in NSCLC remains to be evaluated (56).…”
Section: Exploiting Tumor Biologymentioning
confidence: 99%